(untitled) (Praxis Educativa, 2026)
This study analyses the implementation of Project-Based Learning (PBL) during the pandemic in Chilean educational establishments. Using a qualitative approach that included interviews and narrative productions with teachers and administrators who led the implementation of PBL in their establishments, the conditions, needs and leadership practices that facilitated its adoption and sustainability were examined. The results reveal that PBL emerged in response to urgent educational needs, generating positive impacts on learning, school coexistence, and community engagement. Paradoxically, certain conditions that arose during the crisis (available time, curriculum prioritisation, regulatory flexibility) facilitated its implementation. Post-pandemic sustainability depends on structural and cultural institutional factors, highlighting the crucial role of leadership. It is concluded that PBL proved to be a resilient methodology in adverse contexts, suggesting the need to institutionalise flexible pedagogical practices that strengthen the education system’s responsiveness to future crises.